Closed Transport Engineering of Comet Ornamental Fish (Carassius auratus) using Plant-Based Anesthesia: Effects on Water Quality and Physiological Responses - Henry Kasmanhadi Saputra; Muhammad Subhan Hamka; Wildan Nurussalam; Muhammad Ammar; Eddy Supriyono; Kukuh Nirmala (Politeknik Negeri Sambas, 2025)
Ornamental comet fish are highly sought after by Indonesians and command high prices. These fish are generally distributed throughout Indonesia in plastic bags using closed transportation. Efforts are made to minimize stress on the fish and reduce the deterioration of water quality during transportation by using the chemical MS 222. However, awareness of the side effects of chemicals has led to the need for organic alternatives. One such solution is the bandotan leaf (Ageratum conyzoides), which contains anesthetic properties. The extraction method for bandotan leaves involves maceration, which is the mixing of bandotan leaves and 96% ethanol in a ratio of 7.5:1. A single factor was used in the experimental design, consisting of 3 treatments and 3 replications, totaling 9 experimental units, with statistical analysis conducted using ANOVA. Metabolic waste plays a role in reducing water quality and physiological responses, which can be suppressed by adding bandotan leaf extract. The treatment with the addition of bandotan leaf extract showed superior results in increasing the Survival Rate (SR). Therefore, bandotan leaf has been proven effective in supporting in good water quality and physiological responses of fish.